Recent and Past Governance Reforms in Latin America: What Can We Learn? - Olavarria-Gambi, M (Springer New York LLC, 2019)
By doing a parallel between old and new reforms on governance issues applied in Latin America, this paper seeks to identify learnings as well as to understand what is new and what is not from this type of policy endeavor. The article focuses on the analysis of the State reforms implemented in Latin America during the 1920s and those of the 1990s. It shows that modernization of public administration follows the State reform; that needs calling for modernization are permanent; and that while ends pursued by the State change in the long run, modernization has to be a permanent activity. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.